Mechanisms of Perceived Treatment Assignment and Subsequent Expectancy Effects in a Double Blind Placebo Controlled RCT of Major Depression - Laferton, Johannes A. C.; Vijapura, Sagar; Baer, Lee; Clain, Alisabet J.; Cooper, Abigail; Papakostas, George; Price, Lawrence H.; Carpenter, Linda L.; Tyrka, Audrey R.; Fava, Maurizio; Mischoulon, David (Frontiers in Psychiatry, 2018)
Objective: It has been suggested that patients’ perception of treatment assignment might serve to bias results of double blind randomized controlled trials (RCT). Most previous evidence on the effects of patients’ perceptions and the mechanisms influencing these perceptions relies on cross-sectional associations. This re-analysis of a double blind, placebo controlled RCT of pharmacological treatment of major depression set out to gather longitudinal evidence on the mechanism and effects of patients’ perceived treatment assignment in the pharmacological treatment of major depression. Methods: One-hundred eighty-nine outpatients with DSM-IV diagnosed major depression were randomized to SAMe 1,600-3,200 mg/d, escitalopram 10-20 mg/d, or placebo for 12 weeks. Data on depressive symptoms (17-item Hamilton Depression Scale; HDRS-17), adverse events and patients’ perceived treatment assignment was collected at baseline, week 6, and week 12. The re-analysis focused on N = 166 (out of the originally included 189 participants) with available data on perceived treatment assignment. Results: As in the parent trial, depressive symptoms (HDRS-17) significantly decreased over the course of 12 weeks and there was no difference between placebo, SAMe or escitalopram. A significant amount of patients changed their perceptions about treatment assignment throughout the trial, especially between baseline and week 6. Improvement in depressive symptoms, but not adverse events significantly predicted perceived treatment assignment at week 6. In turn, perceived treatment at week 6 assignment, but not actual treatment, predicted further improvement in depressive symptoms at week 12. Conclusions: The current results provide longitudinal evidence that patients’ perception of treatment assignment systematically change despite a double blind procedure and in turn might trigger expectancy effects with the potential to bias the validity of an RCT.